2014
DOI: 10.5114/cipp.2014.47809
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles and anxiety of rejecters in intimate relationships

Abstract: In this paper, the problem of the lack of stability of intimate female-male relationships, the intensity of which is currently increasing, is presented. Attention is focused on early-childhood attachment styles and anxiety in rejecters in intimate relationships. participants and procedure The research included 120 individuals: 60 individuals who had dropped 3-15 partners (on average, M = 3.77 partners) and 60 individuals from the control group. The following research tools were applied: the Attachment Styles I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
1
0
1
Order By: Relevance
“…A meta-analysis focused on predictors of dissolution of nonmarital romantic relationships in longitudinal studies showed that approximately 34% of young adults' relationships ended between Time 1 and the next assessment (range: 2-77% dissolution) (Le, Dove, Agnew, Korn, & Mutso, 2010). It may be influenced by socio-demographic characteristics, family context, and intrapersonal factors, among others (Mandal & Latusek, 2014;Klimstra et al, 2013). In fact, individuals with stable and well-defined identities are likely to take on adult roles and responsibilities more readily; hence they become involved in more satisfactory and stable romantic relationships (Schwartz, Côté, & Arnett, 2005).…”
Section: Emerging Adulthoodmentioning
confidence: 99%
“…A meta-analysis focused on predictors of dissolution of nonmarital romantic relationships in longitudinal studies showed that approximately 34% of young adults' relationships ended between Time 1 and the next assessment (range: 2-77% dissolution) (Le, Dove, Agnew, Korn, & Mutso, 2010). It may be influenced by socio-demographic characteristics, family context, and intrapersonal factors, among others (Mandal & Latusek, 2014;Klimstra et al, 2013). In fact, individuals with stable and well-defined identities are likely to take on adult roles and responsibilities more readily; hence they become involved in more satisfactory and stable romantic relationships (Schwartz, Côté, & Arnett, 2005).…”
Section: Emerging Adulthoodmentioning
confidence: 99%
“…Diversos hallazgos empíricos identifican variables que matizan la sensibilidad al rechazo amoroso, tal es el caso de los estilos de apego adulto. Las personas con apego ansioso son más sensibles al rechazo que aquellas con apego seguro y son las primeras quienes tienen mayores dificultades en sus relaciones interpersonales (Downey & Feldman, 1996;Sato, Fonagy, & Luyten, 2020;Mandal & Latusek, 2014). Por ora parte, la personalidad puede considerarse un predictor sobre qué tan sensible al rechazo pude ser un individuo (Cavicchioli & Maffei, 2020;Brookings, Zembar, & Hochstetler, 2003).…”
Section: Introductionunclassified